Improving service quality in healthcare organisations through geomarketing statistical tools. Issue 5 (9th October 2017) - Cavallone, Mauro; Magno, Francesca; Zucchi, Alberto
Abstract : Purpose: The purpose of this paper is to demonstrate how geomarketing statical tools (notably, gravitational models) can support healthcare organisations to improve the quality of their services. Design/methodology/approach: Geomarketing tools were applied to the analysis of data (91, 478 observations) concerning the performance of nuclear magnetic resonance. Findings: Geomarketing models can support and enhance the planning of service provisions of healthcare organisations. Drawing the planning actions on the patient needs and actual behaviours allow the healthcare organisations to obtain better market performance. Practical implications: The results support the health service planning activities related to covering the so-called "offer gaps". Originality/value: This is the first study to apply geomarketing to improve the quality of healthcare services.